2008
DOI: 10.1097/mbc.0b013e32830bfdac
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet count on secretion capacity: formulization and use of the formulae for evaluation of platelet secretion in thrombocytopenic patients

Abstract: The correlation between platelet count and bleeding time is nonlinear. The bleeding time prolongs more prominently as platelet count decreases toward 10 000 microl(-1); however, it becomes stable near 100 000 microl(-1). Clinical observations suggest that platelet functional capacity may also play a role in bleeding complications during thrombocytopenia. However, no routine method has been described for evaluation of platelet function during thrombocytopenia. To test if platelet functional capacity is affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(25 reference statements)
1
4
0
2
Order By: Relevance
“…However, we do not agree with their suggestion that their study was the first to examine and define differences in platelet function in patients with equivalent degrees of thrombocytopenia due to ITP or acute myelogenous leukemia/myelodysplastic syndrome (AML/MDS). We have previously proposed a method, depending on lumiaggregometry, for studying platelet functions in thrombocytopenic patients and evaluated platelet dysfunction using this method in AML and ITP too . Our findings were similar to those of Psaila et al .…”
supporting
confidence: 87%
See 1 more Smart Citation
“…However, we do not agree with their suggestion that their study was the first to examine and define differences in platelet function in patients with equivalent degrees of thrombocytopenia due to ITP or acute myelogenous leukemia/myelodysplastic syndrome (AML/MDS). We have previously proposed a method, depending on lumiaggregometry, for studying platelet functions in thrombocytopenic patients and evaluated platelet dysfunction using this method in AML and ITP too . Our findings were similar to those of Psaila et al .…”
supporting
confidence: 87%
“…Moreover, we observed that the test result correlated well with bleeding symptoms. As we previously commented, methods evaluating platelet functions in thrombocytopenic patients could have an impact on platelet transfusion strategies . Further studies are definitely needed on this topic.…”
mentioning
confidence: 92%
“…Platelet granule defects actually seem to be relatively common in pathological states, for example myelodysplastic syndrome . Platelet secretion defects may therefore potentially contribute to bleeding risk in thrombocytopenia .…”
Section: Methods For Measuring Platelet Functionmentioning
confidence: 99%
“…Suskirsčius pacientus į grupes pagal priešoperacinę trombocitų koncentraciją, pacientų grupėje, kurioje buvo trombocitopenija < 60×10 9 /l, pakraujavimų dažnis buvo 100 %, grupėje pacientų, kurių trombocitų kiekis > 60×10 9 /l -6,2 %, p < 0,01, reliatyvi rizika esant trombocitopenijai < 60×10 9 /l padidėja 16 kartų, 95 % PI [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Hemostazės Sutrikimų įTakaunclassified
“…Kraujavimo laikas nerekomenduojamas kaip rutininis patikrinimo testas prieš operaciją, nes chirurginiams pacientams, neturintiems kraujavimo rizikos veiksnių, kraujavimo laikas retai būna kliniškai smarkiai pailgėjęs, prarasto kraujo kiekis ligoniams, turintiems pailgėjusį kraujavimo laiką, neviršija netekto kraujo kiekio ligoniams, turintiems normalų kraujavimo laiką, pailgėjęs kraujavimo laikas nebūtinai yra pagausėjusio kraujavimo priežastis [18]. Kraujavimo laikas priklauso ne tik nuo trombocitų funkcijos, bet ir nuo jų kiekio, smarkiai prailgėja, kai trombocitų koncentracija sumažėja iki 10×10 9 /l, ir stabilizuojasi, kai trombocitų koncentracija yra apie 100×10 9 /l [19].…”
Section: Diskusijaunclassified